Deep-level trap formation in Si-substituted Sr2SnO4:Sm3+ for rewritable optical information storage. (June 2022) - Du, J.; Lyu, S.; Jiang, K.; Huang, D.; Li, J.; Van Deun, R.; Poelman, D.; Lin, H.
Abstract: Persistent luminescent materials containing deep-level traps have attracted extensive research interest in the field of optical information storage due to their unique features of long-lasting emission, energy storage, and controllable photon release upon external stimulations. However, the lack of suitable luminescent materials with deep-level traps is still the bottleneck of such an optical storage application. Herein, we report a series of persistent luminescent materials with reddish-orange emissions and controllable photon release upon thermal stimulation. Through substitution of Sn by Si, more and deeper trap levels are achieved in Sr2 SnO4 :Sm 3+, Si 4+ phosphors. Moreover, both ultraviolet light and high-energy X-ray irradiations can induce reddish-orange emitting persistent luminescence from the as-synthesized samples. Rewritable optical information storage and readout based on photon trapping and de-trapping processes are demonstrated. Optical information can be handily encoded using a commercially available 365 nm light-emitting diode, and decoded upon thermal stimulation. The Sr2 SnO4 :Sm 3+, Si 4+ phosphors as presented in this work show a great promise for rewritable optical data storage and information encryption. Graphical abstract: Through substitution by Si, persistent luminescent materials with reddish-orange emissions and deep-level traps are achieved in Sr2 SnO4 :Sm 3+, Si 4+ phosphors. Based on photon trapping and de-trapping processes, information can be encoded by UV light/X-ray and decoded upon thermal stimulation. The as-developed material in this work shows a great promise for rewritable optical information storage and data encryption. Image 1 Highlights: Reddish-orange emissions and deep-level traps are achieved in Sr2 SnO4 :Sm 3+, Si 4+ . Information can be encoded by UV-light/X-ray and decoded upon thermal stimulation. Rewritable optical information storage and data encryption are demonstrated.